Polar knowledge of US students as indicated by an online Kahoot! quiz game. Issue 2 (3rd April 2021) - Pfirman, Stephanie; Hamilton, Lawrence; Turrin, Margie; Narveson, Craig; Lloyd, Carrie A.
Abstract: This first analysis of aggregated data from the Kahoot! game-based player response system demonstrates that it can provide assessments of overall US student polar knowledge and identifies differences in polar knowledge across several states. A kahoot online quiz on polar topics recorded over 25, 000 United States teacher-hosted classroom players (mostly middle-high school students) run by 1, 167 unique teacher hosts within nine months (09/2018 through 06/2019). This high volume of teacher-initiated kahoots shows that many US teachers are motivated to include polar content in their teaching. We selected a subset of questions for analysis to compare with external data from a 2016 survey assessing polar knowledge of the US adult public. On three directly comparable questions kahoot student accuracy averaged just 30%, well below the 49% average accuracy observed on the nationwide survey of adults. Our geographic analysis focused on 13 states that had greater than 100 players for all questions analyzed. Among these, students in Rhode Island, Oregon, Arizona, and Washington exhibit the highest scores overall, while responses from Ohio and Illinois students appeared no better than guessing. Although widespread US teacher interest in polar content is indicated by the many who chose to use the polar kahoot in their classroom, students' polar knowledge proves to be very low. These findings reinforce a need to include more polar and Earth system content in curricula, as well as to crowdsource benchmarked suites of knowledge questions appropriate for assessment of educational interventions.